MIS 5e relative sea-level changes in the Mediterranean Sea: Contribution of isostatic disequilibrium. (1st April 2018) - Stocchi, Paolo; Vacchi, Matteo; Lorscheid, Thomas; de Boer, Bas; Simms, Alexander R.; van de Wal, Roderik S.W.; Vermeersen, Bert L.A.; Pappalardo, Marta; Rovere, Alessio
Abstract: Sea-level indicators dated to the Last Interglacial, or Marine Isotope Stage (MIS) 5e, have a twofold value. First, they can be used to constrain the melting of Greenland and Antarctic Ice Sheets in response to global warming scenarios. Second, they can be used to calculate the vertical crustal rates at active margins. For both applications, the contribution of glacio- and hydro-isostatic adjustment (GIA) to vertical displacement of sea-level indicators must be calculated. In this paper, we re-assess MIS 5e sea-level indicators at 11 Mediterranean sites that have been generally considered tectonically stable or affected by mild tectonics. These are found within a range of elevations of 2–10 m above modern mean sea level. Four sites are characterized by two separate sea-level stands, which suggest a two-step sea-level highstand during MIS 5e. Comparing field data with numerical modeling we show that (i) GIA is an important contributor to the spatial and temporal variability of the sea-level highstand during MIS 5e, (ii) the isostatic imbalance from the melting of the MIS 6 ice sheet can produce a >2.0 m sea-level highstand, and (iii) a two-step melting phase for the Greenland and Antarctic Ice Sheets reduces the differences between observations and predictions. Our results show that assumptions of tectonic stability on the basis of the MIS 5e records carry intrinsically large uncertainties, stemming either from uncertainties in field data and GIA models. The latter are propagated to either Holocene or Pleistocene sea-level reconstructions if tectonic rates are considered linear through time.